2009
DOI: 10.1890/08-2236.1
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolating population size from the occupancy–abundance relationship and the scaling pattern of occupancy

Abstract: Abstract. The estimation of species abundances at regional scales requires a cost-efficient method that can be applied to existing broadscale data. We compared the performance of eight models for estimating species abundance and community structure from presenceabsence maps of the southern African avifauna. Six models were based on the intraspecific occupancy-abundance relationship (OAR); the other two on the scaling pattern of species occupancy (SPO), which quantifies the decline in species range size when me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 74 publications
0
67
1
Order By: Relevance
“…Such non-process based methodology emphasizes on crossscale pattern consistency and constraints (e.g. Hui et al 2006;Hui 2009;Harte 2011) and has been shown to outperform many process-based methods for inferring fine scale occupancies and abundances (Hui et al 2009;Barwell et al 2014). Such inferences reflect the most probable or likely predictions without additional information/processes assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Such non-process based methodology emphasizes on crossscale pattern consistency and constraints (e.g. Hui et al 2006;Hui 2009;Harte 2011) and has been shown to outperform many process-based methods for inferring fine scale occupancies and abundances (Hui et al 2009;Barwell et al 2014). Such inferences reflect the most probable or likely predictions without additional information/processes assumed.…”
Section: Discussionmentioning
confidence: 99%
“…It has many merits (Hui et al 2009), but would have been difficult to apply in the present case. In fact, at each resolution it needs spatially explicit occupancy information that is not available in many data sets as well as in the empirical data we considered in this study.…”
mentioning
confidence: 87%
“…In recent years the issue of species occupancy at different spatial scales has been of growing interest in spatial ecology (Kunin 1998, He and Gaston 2000, Kunin et al 2000, Tosh et al 2004, Hui et al 2009). Species occupancy, or the fraction of area occupied by a given species, is obtained by dividing the study area into an artificial regular grid of cells of (ideally) equal size and then calculating the fraction of such cells occupied by a focal species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, abundance is more readily estimated from the invaded area (i.e. condensed area or the net area of infestation) (Hui et al 2009). This, in essence, is a measure of extent-area of occupancy (AOO) at a fine spatial scale-but as a simple metric of relative abundance for invasive populations it provides a useful link to impact and management.…”
Section: Estimating Current Impactsmentioning
confidence: 99%